2021
DOI: 10.1371/journal.pone.0247205
|View full text |Cite
|
Sign up to set email alerts
|

An integrated clinical and genetic model for predicting risk of severe COVID-19: A population-based case–control study

Abstract: Up to 30% of people who test positive to SARS-CoV-2 will develop severe COVID-19 and require hospitalisation. Age, gender, and comorbidities are known to be risk factors for severe COVID-19 but are generally considered independently without accurate knowledge of the magnitude of their effect on risk, potentially resulting in incorrect risk estimation. There is an urgent need for accurate prediction of the risk of severe COVID-19 for use in workplaces and healthcare settings, and for individual risk management.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…Epidemiological analyses have recognised that male sex and increasing age are risk factors for severe COVID-19 and that common medical comorbidities contribute to individual risk [ 6 – 8 ]. Our previous analysis showed that the effects of sex and age are attenuated when comorbidities are taken into account [ 9 ]. The effect of human genetic variation on COVID-19 severity has been examined by the COVID-19 Host Genetics Initiative, which has now released several meta-analyses of the available genome-wide association studies of COVID-19 severity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological analyses have recognised that male sex and increasing age are risk factors for severe COVID-19 and that common medical comorbidities contribute to individual risk [ 6 – 8 ]. Our previous analysis showed that the effects of sex and age are attenuated when comorbidities are taken into account [ 9 ]. The effect of human genetic variation on COVID-19 severity has been examined by the COVID-19 Host Genetics Initiative, which has now released several meta-analyses of the available genome-wide association studies of COVID-19 severity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously developed a prototype risk model [ 9 ] based upon early data from the UK Biobank [ 16 , 17 ] and SNPs identified from the COVID-19 Host Genetics Initiative Release 2 meta-analysis of hospitalised vs. non-hospitalised COVID-19 cases (which was at that time almost exclusively UK Biobank samples) [ 10 , 18 ]. Our prototype model appeared to perform well but was based on a small sample size from the first wave of the pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33In the development of the new model, the strongest risk factor was respiratory disease (with an odds per standard deviation of 1.35;Table 3). The older age groups (70-74, 75-79, and 80+ years) and being male all had odds per standard deviations of 1.20 to1.29. The other risk factors (the seven SPNs, ethnicity, body mass index, cancer history (haematological and non-haematological), cerebrovascular disease, diabetes, hypertension, and kidney disease) all had odds per adjusted standard deviations in the range 1.07 to 1.13 (or the equivalent protective effect).…”
mentioning
confidence: 96%
“…The COVID-19 pandemic continues to dominate global public health, with countries having varying success with infection control measures and social distancing protocols, 1 Coupled with this are the logistical challenges with the distribution of vaccines 2 and the emergence of SARS-CoV-2 variants of concern. 3,4 Of those who become infected with SARS-CoV-2, 10%-15% will develop severe COVID-19 requiring hospitalisation and 5%…”
mentioning
confidence: 99%